O Auto da Vaca-Bumbá Rosinha Cheirosa: O Manejar da Encenação da Companhia Teatral Quixotes Del grão Pará - SANTOS, Murilo Ferreira (2021)
This work has as its theme: The Auto da Bumbá Cow Rosinha Smell: The management of the staging of the Quixotes Del grain Pará Theater Company. In which it is investigated through participatory observation the staging processes of the Auto da Bumbá Rosinha Smell. It is created as a cultural identity through poetic ethnomethodology in accordance with the memory of the playwright / director Admilson Medeiros as motto for the emergence of the group and later of the Self. The project consists of three stages: The handling of pickets, understanding the management of the construction of the Auto and the role of staging in this context having as its main author the director of the group; The pasture, having the understanding of the procession staging of the dramaturgy of the procession to the participant observation dialoguing with the staging script along with the dramaturgical text, the descriptions of the activities, interview with the director / director of the Auto da VacaBumbá, of the children, things heard, felt. By contrast I bridge Viola Spolin - Improvisation to the theater by discovering methods possibly used by the director and The Cowgirl's Milk Rosinha Cheirosa, bringing the understanding of “community” from The Time of the Tribes - The Decline of Individualism in Mass Societies Michel Maffesoli, making the subject have a dynamic approach, because it tends to a sharper vision of the creation of new imaginary sociability and referring to the postmodern micro society, where the community (tribes) is formed in networks by their own will have fun and create sharing opinions, values and aesthetic tastes.